Green-emitting Lu3Al5O12:Ce3+ phosphor as a visible light amplifier for dye-sensitized solar cells1. Issue 31 (8th April 2015) - Han, Gill Sang; Song, Young Hyun; Kim, Dong Hoe; Lee, Min-Ji; Lee, Dong Geon; Han, Se-Hoon; Kim, Yongjoo; Jung, Mong-Kwon; Yoon, Dae-Ho; Jung, Hyun Suk
<x xml:space="preserve">Abstract</x> A down convertor Lu3Al5O12:Ce3+ (LuAG) phosphor was used as a visible light amplifier for dye-sensitized solar cells (DSSCs).